Intellectual Property Rights Education as a General Compulsory Subject in Higher Education - M Hudi Asrori S; Dona Budi Kharisma (Postgraduate, University of Mataram, 2023)
In several developed countries such as the United States of America (USA), Japan, and the United Kingdom, Intellectual Property Rights (IPR) education has an important role in empowering IPR. The existence of HKI education also increases the growth of the creative economy. Therefore, the creative economy sector is growing rapidly and contributing significantly to Gross Domestic Product (GDP), labor absorption, and exports. However, it is different from the people in Indonesia who still lack understanding and awareness of IPR. On the one hand, IPR has moral and economic values that must be protected. This paper aims to examine the urgency of HKI as a compulsory subject in universities in Indonesia This type of research is legal research using a comparative approach. The data collection technique was carried out by means of a literature study. Data analysis techniques were carried out using normative juridical methods. The results of the study stated that HKI has an urgency as a compulsory subject in tertiary institutions due to several things, first, innovations and research results produced in tertiary institutions are HKI objects that must be protected. In addition to encouraging innovation, this is intended so that inventors and creators can have moral and economic values for their findings. Second, the prevalence of IPR violations in tertiary institutions is an indication of the importance of IPR Education as a general compulsory subject. Third, downstream research results. The main asset in downstream research results is intellectual property owned by creators and inventors. The results of higher education research are the values of originality, innovation, and uniqueness that require the protection of intellectual property. IPR education can be a medium to increase awareness of legal protection for a research result produced by academics.